How do you simplify (((-m^4)(p^4)(q^4))^-1 ) /((m)(q)(p^3) x (m^3)(p^-3)(q^-1)?

2 Answers
Jun 25, 2017

color(blue)(1/(-m^8p^4q^4x)

Explanation:

((-m^4)(p^4)(q^4))^-1/((m)(q)(p^3)x(m^3)(p^-3)(q^-1))

:.=(1/(-m^4*p^4*q^4))/(m*q*p^3*x*m^3*p^-3*q^-1)

:.=(1/(-m^4*p^4*q^4))/(m^(1+3)*q^(1-1)*p^(3-3)*x)

:.=(1/(-m^4*p^4*q^4))/(m^4*q^0*p^0*x)

:.=(1/(-m^4*p^4*q^4))/(m^4*1*1*x)

:.=(1/(-m^4*p^4*q^4))/(m^4*x)

:.=1/(-m^4*p^4*q^4) xx 1/(m^4*x)

:.=1/(-m^(4+4)*p^4*q^4*x)

:.color(blue)(=1/(-m^8*p^4*q^4*x)

Jun 25, 2017

-1/(m^8p^4q^4)

Explanation:

I suspect the x was meant to be xx?

Simplify where possible first in the numerator and denominator separately.

((-m^4)(p^4)(q^4))^-1/((m)(q)(p^3)xx(m^3)(p^-3)(q^-1))

=((-m^-4)(p^-4)(q^-4))/((m^4)(q^0)(p^0))" "(larr"multiply the indices by -1")/(larr "add the indices of like bases")

x^0 = 1 and x^-m = 1/x^m

-1/(m^4 m^4p^4q^4)

-1/(m^8p^4q^4)